Identification of differentially regulated genes in breast (MCF-7) and lung (H1299) cancer cell lines during Newcastle disease virus strain AF2240 infection - Roslan, Nurhidayah (2012)
Newcastle disease virus (NDV), a member of Paramyxoviridae family is known for its selective oncogenic effects in cancer cells. Even though NDV infections in cancer cells were shown to result in cell death through apoptosis, the actual mechanism of NDV-induced cell death process has not been thoroughly investigated. Therefore, in the present study, we investigated the effects of infection of a local velogenic NDV strain, designated as AF2240, on gene and cell cycle regulation of cancer cells. Two different cancer cell lines; MCF-7 breast cancer cell line with wild type p53 status,and H1299, a non-small cell lung cancer (NSCLC) cell line with p53-null were used. At 1 MOI, NDV AF2240 infection resulted in cellular morphological changes as early as 3 HPI in both MCF-7 as well as H1299 cells. At this time, viral proteins were also began to be detectable via immunoblotting. The infection caused massive cell death via apoptosis in MCF-7 cells by 12 HPI. The lack of p53 tumor suppressor protein in H1299 led to reduced apoptosis in H1299 cells. The cells however died through necrosis after 12 hours post infection (HPI). These findings showed that NDV can induce apoptosis in both p53-dependent and p53-independent manner, although the former is more efficient. Despite the p53-dependency, EIF4A1, a member of the RNA helicase family is crucial in NDV-induced cell death. Overexpression of EIF4A1 led to increase in translation of viral proteins. The increase in NDV viral proteins caused cells to trigger cell cycle arrest via upregulation of p21Cip1 and p27Kip1. The present of high levels (more than 0.5 fold) of these cyclin dependent kinase inhibitors at early stages of infection caused ploidy increase in MCF-7. In H1299, growth arrest at G0/G1 phase was observed. Another important protein that was found to be involved in NDV-induced cancer cell killing was MBP-1. Due to the difference in the p53 status in MCF-7 versus H1299, the effects of MBP-1 regulation might be different. Since MBP-1 involves in both apoptotic as well as necrotic cell death pathways, the outcome of NDV infection in the cells were different. In MCF-7, NDV AF2240 infection caused massive apoptosis but not in H1299 cells. This study started with preparation of pure virus and cell lines. Then the cells were either infected with NDV or mock-infected using saline and media. The cells were then harvested at different post-infection period (3, 6, 9, and 12 hours) where unlysed cells were used in apoptosis analysis using TUNEL assay and Typan blue staining method as well as in cell cycle analysis. Whereas, RNA and total lysate from lysed cells were subjected to GeneFishing, Real-time PCR and Western blotting. Results obtained in this study showed that the outcome of NDV infection strongly depends on the genetic status of cell lines. This stresses the complexity of the pathways involve in NDV oncolytic properties. Nonetheless, our study has shed some light into further understanding of the effects of NDV on the gene and cell cycle regulation of MCF-7 and H1299 cells. Further studies however are needed in order to ensure the efficacy and efficiency of NDV as a potential anti-cancer agent for specific cancer types.